OS11.5.A PATZ1 fusions define a novel molecularly distinct CNS tumor entity with a broad histological spectrum. (9th September 2021) - Al Halabi, K T; Sievers, P; Stichel, D; Sommerkamp, A C; Sill, M; Jäger, N; Wittmann, A; Kramm, C; Snuderl, M; Pfister, S M; von Deimling, A; Sahm, F; et al.
Abstract: BACKGROUND: DNA methylation profiling has emerged as a useful tool for robust classification of rare CNS tumors with a broad morphological spectrum. Routine diagnostic molecular profiling performed in Heidelberg and at international collaborating centers revealed a small but recurring number of CNS tumors with fusions of the PATZ1 gene coupled to either MN1 or EWSR1, displaying a distinct genome-wide methylation profile; indicating that these tumors could form a seperate biological entity. MATERIAL AND METHODS: We obtained genome-wide DNA-methylation array profiling of 68 primary CNS tumors. RNA-sequencing was perfomed on (n=23/68, 34%) of the tumor samples, including (n=6) from fresh frozen tissue used for gene expression profiling. For n=3 cases, whole exome sequencing (WES) data was generated, and gene panel sequencing data was available for n=13 cases, We systematically reevaluated the histopahthological features of 14 tumors, while immunohistochemical (IHC) staining with Ki-67, GFAP, MAP2, NeuN, Olig-2, Synaptophysin, S-100 and Vimentin was performed for (n=12) tumors. We finally collected clinical data to preliminarily characterize this novel tumor entity. RESULTS: A selected analysis of the tumors in this novel cohort (n=68), compared with a reference cohort consisting of 15 other low- and high-grade glial and glioneuronal tumor classes, confirmed a clearly distinct grouping. No similarity was seen with the MN1:BEND2 and MN1:CXXC5-fused CNS-tumors. Analysis of Copy number profiles derived from the DNA-methylation data showed a mostly quite genome, with (n=64/65, 98%) of tumors showing copy number variations on Chromosome 22. RNA-sequencing detected PATZ1 fusions in all tumors sequenced (n=12; MN1:PATZ1, n=11; EWSR1:PATZ1). IGF2, PAX2 and GATA2, all genes involved in brain stem cell biology, were upregulated compared to a combined reference cohort of other glioma subtypes. DNA-sequencing showed no relevant alterations at the level of point mutations or small insertions/deletions. The tumors in our cohort showed polyphenotypic histologies along the glial spectrum, with a subset of tumors being diagnosed as Gliobastoma, WHO Grade 4 and bi- and multiphasic differentaion patterns being evident. IHC performed on tissue available did not favor a particular lineage, with most tumors showing immunopositivity to GFAP. Reverse translation of the gene expression data showed a potential role for NG2 as immunostaining marker. The median age was 11.0 years (0–80), (MN1:PATZ1 manifested at a younger age (median = 4 years) vs EWSR1:PATZ1 (median = 14 years)). Median PFS was 12 months. CONCLUSION: We describe here a novel, molecularly distinct CNS tumor class with strikingly variable histopathologic morphology. We postulate that the PATZ1 fusions are a key driver of tumor initiation. Preliminary indications suggest an intermediate prognosis.